Microinstability simulations for stellarators involving kinetic electrons and realistic profiles. (1st October 2022) - Riemann, J; Kleiber, R; Borchardt, M; Slaby, C
Abstract: In this work, linear simulation results obtained with the global particle-in-cell code EUTERPE are applied to plasmas with both adiabatic and kinetic electrons in a Wendelstein 7-X magnetic configuration. Special attention is paid to challenges arising from the need to design realistic and consistent gradient scans on realistic profiles used in global simulations. Results obtained in a pressure-preserving gradient scan performed with kinetic electrons suggest a strong impact of a finite density gradient on the growth of electron-driven instabilities below the ion-temperature-gradient stability limit. Power transfer diagnostics are used to identify the nature of the coexisting driving mechanisms.